PENGENTASAN KEMISKINAN MELALUI PEMBANGUNAN JARINGAN EKONOMI PEDESAAN (Sebagai Suatu Strategi)* - Prijono Tjiptoherijanto (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 1997)
Various policies have been implemented by Indonesian government in its efforts to eliminate poverty. This paper proposes BKKBN's (National Family Planning Coordinating Agency) attempts which stress on poverty elimination in non-backward area by way of prosperous family development through expanding rural economic network. The program is started with improving movement of